Clinical and economic burden of acute otitis media caused by Streptococcus pneumoniae in European children, after widespread use of PCVs-A systematic literature review of published evidence. - Heloisa Ricci Conesa; Helena Skröder; Nicholas Norton; Goran Bencina; Eleana Tsoumani (PLoS ONE)
Background Acute otitis media (AOM) is a common childhood disease frequently caused by Streptococcus pneumoniae. Pneumococcal conjugate vaccines (PCV7, PCV10, PCV13) can reduce the risk of AOM but may also shift AOM etiology and serotype distribution. The aim of this study was to review estimates from published literature of the burden of AOM in Europe after widespread use of PCVs over the past 10 years, focusing on incidence, etiology, serotype distribution and antibiotic resistance of Streptococcus pneumoniae, and economic burden. Methods This systematic review included published literature from 31 European countries, for children aged ≤5 years, published after 2011. Searches were conducted using PubMed, Embase, Google, and three disease conference websites. Risk of bias was assessed with ISPOR-AMCP-NPC, ECOBIAS or ROBIS, depending on the type of study. Results In total, 107 relevant records were identified, which revealed wide variation in study methodology and reporting, thus limiting comparisons across outcomes. No homogenous trends were identified in incidence rates across countries, or in detection of S. pneumoniae as a cause of AOM over time. There were indications of a reduction in hospitalization rates (decreases between 24.5-38.8% points, depending on country, PCV type and time since PCV introduction) and antibiotic resistance (decreases between 14-24%, depending on country), following the widespread use of PCVs over time. The last two trends imply a potential decrease in economic burden, though this was not possible to confirm with the identified cost data. There was also evidence of an increase in serotype distributions towards non-vaccine serotypes in all of the countries where non-PCV serotype data were available, as well as limited data of increased antibiotic resistance within non-vaccine serotypes. Conclusions Though some factors point to a reduction in AOM burden in Europe, the burden still remains high, residual burden from uncovered serotypes is present and it is difficult to provide comprehensive, accurate and up-to-date estimates of said burden from the published literature. This could be improved by standardised methodology, reporting and wider use of surveillance systems.